The Policy Analysis for Implementation of Mass Drug Administration of Filariasis: A Health Policy Triangle Framework - Ikrimah Nafilata; Dumilah Ayuningtyas; Tri Yunis Miko Wahyono (JURNAL INFO KESEHATAN, 2026)
Lymphatic filariasis is a neglected tropical disease targeted for elimination through the World Health Organization’s Global Programme to Eliminate Lymphatic Filariasis (GPELF), primarily via annual Mass Drug Administration (MDA) in endemic areas with microfilaria rates exceeding 1%. This study aims to analyze the implementation of filariasis MDA using the Ivermectin–Diethylcarbamazine–Albendazole (IDA) regimen through the Health Policy Triangle framework, focusing on policy content, context, process, and actors. A qualitative policy analysis was conducted using data from publicly available policy documents, relevant empirical literature, and in-depth interviews with key stakeholders in selected districts/cities implementing extended IDA-based MDA. This study involved 6 participants, including 3 local leaders in community mobilization and health promotion, and 3 residents. The analysis specifically examined the adequacy of Health Operational Assistance (BOK) funding and the effectiveness of community socialization strategies. Findings highlight gaps in funding flexibility and uneven dissemination of information, which contribute to suboptimal treatment coverage. Strengthening financial support mechanisms and implementing more equitable and context-sensitive socialization models are essential to improve the effectiveness of IDA-based MDA and accelerate progress toward filariasis elimination.